The growth of salaries and benefits in the federal government, state and local governments and public education, 1998-2017 - Andrew G. Biggs (American Enterprise Institute (AEI), 2019)
Data from the National Income and Product Accounts published by the US federal government make it possible to analyze the growth of state and local government employee compensation by state.
Keywords: A; 330; Retirement; pensions